Evaluación de la semilla de moringa oleifera como coagulante para el tratamiento de aguas residuales de la PTAR El Salitre (2021)
For wastewater treatment, one of the main processes is coagulation and flocculation. In order to develop this process, the use of an external agent called coagulant is required. Normally these compounds are of chemical origin; however, nowadays many of them are harmful to human health and the environment. For this reason, compounds of natural origin have been studied that can have a similar or better performance with respect to the removals presented by chemical coagulants.